Plasma brain derived neurotrophic factor (BDNF) and response to ketamine in treatment-resistant depression. (February 2014) - Haile, C. N.; Murrough, J. W.; Iosifescu, D. V.; Chang, L. C.; Al Jurdi, R. K.; Foulkes, A.; Iqbal, S.; Mahoney, J. J.; De La Garza, R.; Charney, D. S.; Newton, T. F.; Mathew, S. J.
Abstract Ketamine produces rapid antidepressant effects in treatment-resistant depression (TRD), but the magnitude of response varies considerably between individual patients. Brain-derived neurotrophic factor (BDNF) has been investigated as a biomarker of treatment response in depression and has been implicated in the mechanism of action of ketamine. We evaluated plasma BDNF and associations with symptoms in 22 patients with TRD enrolled in a randomized controlled trial of ketamine compared to an anaesthetic control (midazolam). Ketamine significantly increased plasma BDNF levels in responders compared to non-responders 240 min post-infusion, and Montgomery–Åsberg Depression Rating Scale (MADRS) scores were negatively correlated with BDNF (r=−0.701, p = 0.008). Plasma BDNF levels at 240 min post-infusion were highly negatively associated with MADRS scores at 240 min (r = −0.897, p=.002), 24 h (r = −0.791, p = 0.038), 48 h (r = −0.944, p = 0.001) and 72 h (r = −0.977, p = 0.010). No associations with BDNF were found for patients receiving midazolam. These data support plasma BDNF as a peripheral biomarker relevant to ketamine antidepressant response.